Massive lymphadenopathy and hypereosinophilia in cd5-negative small lymphocytic lymphoma - Shweta Pal; Michael Leonard Anthony; Rituparna Chetia; Uttam Kumar Nath; Ashok Singh; Harish Chandra (Journal of Applied Hematology, 2019)
Small lymphocytic lymphoma (SLL) is a relatively rare B-cell non-Hodgkin lymphoma that is considered to be the tissue equivalent of the much more common entity chronic lymphocytic leukemia (CLL). Most patients with SLL present with indolent generalized lymphadenopathy, which has frequently been present for several years. We hereby describe an unusual case of SLL in a patient who presented with a huge swelling at the right shoulder region and a single right enlarged axillary lymph node. The other uncommon findings were the presence of peripheral blood hypereosinophilia and CD5 immunonegativity.